2018
DOI: 10.1111/apa.14592
|View full text |Cite
|
Sign up to set email alerts
|

The impact and understanding of childhood drowning by a community in West Bengal, India, and the suggested preventive measures

Abstract: Aim Our aim was to improve our understanding of the contextual factors contributing to child drowning in rural West Bengal, India. Methods This 2017 study used interviews, focus groups and observations and the participants included community leaders, household heads, parents and children aged 7–17 years from three remote villages. They included adults and children who had been directly affected by the loss of family members or friends. Results We conducted 19 in‐depth interviews, six focus groups and three inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Participants also noted the need for complementary awareness activities, such as to dispel improper beliefs around effective child rescue techniques. Common responses to child drowning incidents involve engaging local quack doctors to perform rituals and trying to remove water by spinning the child over an adult’s head [ 7 , 29 ]. Changing problematic norms and beliefs is an important step in behaviour change, and Sundarbans communities must be informed that such actions do not save children [ 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants also noted the need for complementary awareness activities, such as to dispel improper beliefs around effective child rescue techniques. Common responses to child drowning incidents involve engaging local quack doctors to perform rituals and trying to remove water by spinning the child over an adult’s head [ 7 , 29 ]. Changing problematic norms and beliefs is an important step in behaviour change, and Sundarbans communities must be informed that such actions do not save children [ 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…These interventions are: the installation of home-based barriers controlling access to water (such as playpens and door barriers), the provision of supervised safe spaces with capable child care, teaching school-aged children basic swimming and rescue skills and training adult bystanders in rescue and resuscitation [ 1 ]. Previous research has shown that communities in the Sundarbans consider drowning a health issue [ 7 ]. Despite this perception and the high rates of drowning, there are no preventive measures implemented in the region.…”
Section: Introductionmentioning
confidence: 99%
“…A household experiences catastrophic health expenditure (CHE) if the health care payment exceeds a threshold (x%) of the total household consumption expenditure ie OOPE>x% HCE or Share of out-of-pocket expenditure on total household expenditure >x%. Various studies have stipulated this threshold based on various theories [ 20 , 24 26 ]. This study has used two approaches to determine the CHE.…”
Section: Outcome Indicatorsmentioning
confidence: 99%